Aggressive nasopalatine duct cyst with nasal involvement - Divya Pandya; Soumadip Dey; Maumita Bhattacharya; Pooja Singh (International Journal of Medical Research and Review, 2018)
Nasopalatine duct cyst is a non-odontogenicdevelopmental cyst typically located in the maxillary midline between the tooth roots of central incisors, these cysts are infrequent and can often be misdiagnosed as periapical lesion or cyst. In this article, we present a case of which was clinically and radiographicallyprovisionally diagnosed as nasopalatine duct cyst in a 62 year old male patient with complaint of swelling in midline of palate. The lesion was surgically removed, and histopathologically confirmed the provisional diagnosis, thus concluding that it can be a diagnostic dilemma in clinical and radiological examinations.